2021
DOI: 10.1038/s41419-020-03380-2
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase KDM4C controls tumorigenesis of glioblastoma by epigenetically regulating p53 and c-Myc

Abstract: Glioblastoma is the most lethal brain tumor and its pathogenesis remains incompletely understood. KDM4C is a histone H3K9 demethylase that contributes to epigenetic regulation of both oncogene and tumor suppressor genes and is often overexpressed in human tumors, including glioblastoma. However, KDM4C’s roles in glioblastoma and the underlying molecular mechanisms remain unclear. Here, we show that KDM4C knockdown significantly represses proliferation and tumorigenesis of glioblastoma cells in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…We found that silencing KDM4C suppressed the proliferation and migration ability of multiple myeloma cells. These results were consistent with the previous studies 6,20,21) . Lee et al found that down-regulation of KDM4C inhibited proliferation and tumorigenesis of glioblastoma cells 20) .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that silencing KDM4C suppressed the proliferation and migration ability of multiple myeloma cells. These results were consistent with the previous studies 6,20,21) . Lee et al found that down-regulation of KDM4C inhibited proliferation and tumorigenesis of glioblastoma cells 20) .…”
Section: Discussionsupporting
confidence: 94%
“…These results were consistent with the previous studies 6,20,21) . Lee et al found that down-regulation of KDM4C inhibited proliferation and tumorigenesis of glioblastoma cells 20) . Lin et al revealed that KDM4C knockdown suppressed proliferation and soft agar colony formation ability of prostate cancer cells 6) .…”
Section: Discussionsupporting
confidence: 94%
“…D609 suppressed ßFGF-stimulated astrocyte spread, probably due to SMS inhibition and an elevation in levels of ceramide [ 49 ]. By inhibiting SMS and upregulating the cyclin-dependent kinase (Cdk) inhibitors p27 and p21, D609 can cause the cell-cycle arrest and increase ceramide levels [ 50 , 51 , 52 ]. Ceramide may stimulate p27 and p21 expression by activating c-myc regulating protein phosphatase 2A (PP2A), which suppresses p21 and p27 expression [ 53 ].…”
Section: Mechanism Of Action Of D609mentioning
confidence: 99%
“…Ciclopirox targets KDM4B, inhibiting MYC signaling pathways and tumor growth in MYC-driven neuroblastomas [158]. SD70, a KDM4C-selective inhibitor, represses MYC transcription and activates p53, inducing apoptosis in glioblastoma [159].…”
Section: Targeting Epigenetic Mechanisms Controlled By Mycmentioning
confidence: 99%